The Effect of Global Commodity Price Volatility on Indonesia's Trade Balance - Ummy Kalsum; Nasrullah Djamil; Tiara Nirmala; Septi wifasari; IGP Ratih Andaningsih (Nomico, 2025)
Indonesia is a country that is highly dependent on the export of primary commodities, such as crude oil, coal, and palm oil (CPO), so that global price fluctuations have a significant impact on the national trade balance. This study aims to analyze the effect of price volatility of these three main commodities on Indonesia's trade balance and evaluate the role of the exchange rate as a control variable. The method used is a quantitative approach with multiple linear regression analysis and the ARCH/GARCH volatility model, using annual data from 2010 to 2024. The results of the analysis show that crude oil price volatility has the largest and most significant impact on the decline in the trade surplus (coefficient -0.58, p < 0.01), followed by coal (-0.42, p < 0.05) and CPO (-0.29, p < 0.1). The GARCH(1,1) model confirms that price volatility is persistent, especially for oil and coal, which means that past price fluctuations influence future volatility. Furthermore, the rupiah exchange rate proved significant as a control variable (–0.37, p < 0.05), reinforcing the negative impact of price fluctuations on trade. The study's conclusions emphasize the importance of export diversification strategies, downstreaming commodity industries, and strengthening risk mitigation instruments such as hedging and exchange rate stabilization in maintaining Indonesia's trade resilience.